Alemtuzumab versus antithymocyte globulin induction therapies in kidney transplantation patients: A systematic review and meta-analysis of randomized controlled trials. Issue 28 (July 2017) - Zheng, Jianming; Song, Wenli
Abstract : Abstract: Alemtuzumab (ALEM) is widely used as an induction therapy for organ transplantation, and numerous randomized controlled trials (RCTs) have been published to evaluate its efficacy and safety in kidney transplantation as compared with antithymocyte globulin (ATG). The purpose of this study was to compare the benefits and safety of ALEM with those of ATG for induction therapy. A systematic literature search in three electronic databases, including PubMed, EmBase, and Cochrane Library, since inception through October 2016, was conducted to identify potential RCTs for inclusion. Trials that investigated the risk of biopsy-proven acute rejection (BPAR), mortality, graft failure, delayed graft function (DGF), chronic allograft nephropathy (CAN), infections, cytomegalovirus (CMV) infections, new-onset diabetes mellitus after transplant (NODAT), and granulocyte colony stimulation factor (GCSF) use in kidney transplant recipients who received ALEM or ATG as an induction therapy were included. Relative risk (RR) and 95% confidence intervals (CIs) were calculated using a random-effects model. Six RCTs involving 446 kidney transplantation patients were included in this meta-analysis. The effects of ALEM therapy were not significantly different from those of ATG therapy, including the incidence of BPAR (RR: 0.77; 95% CI: 0.51–1.18; P  = .229), mortality (RR: 0.64; 95% CI: 0.30–1.39; P  = .263), graft failure (RR: 0.81; 95% CI: 0.49–1.33; P  = .411), DGF (RR: 1.00; 95% CI: 0.60–1.67; P  = .999), CAN (RR: 1.42; 95% CI: 0.44–4.57; P  = .556), infections (RR: 1.00; 95% CI: 0.74–1.35; P  = .989), CMV infections (RR: 0.70; 95% CI: 0.38–1.30; P  = .263), NODAT (RR: 0.50; 95% CI: 0.18–1.36; P  = .174), and GCSF use (RR: 1.16; 95% CI: 0.81–1.66; P  = .413). Sensitivity analyses were consistent with the overall analysis for all effects except CAN, suggesting that the risk of CAN might be higher with ALEM therapy than ATG therapy (RR: 2.45; 95% CI: 1.02–5.94; P  = .046). The findings of this study suggest that the beneficial effects of ALEM therapy are greater than those of ATG therapy in kidney transplantation patients; however, the effects were not statistically significant because of the limited number of trials. Further large-scale RCTs are needed to verify the treatment effects of ALEM.